URGENSI WAQAF DALAM MENGATASI PERMASALAHAN KEMISKINAN DI INDONESIA: LITERATURE REVIEW - Kholid Musana; Syaeful Bahri (Media Mahardhika, 2023)
Waqf plays an important role in advancing the economy and prospering Muslims in many places in the world. The purpose of this study is to analyze the literature related to waqf for poverty alleviation. The method used in this study is a narrative review study, where this method approach is based on the literature review method which is carried out systematically to collect, evaluate, and present findings from various studies conducted by other previous studies. Based on the results of the study revealed that in eradicating poverty, one cannot only depend on zakat. But it is also necessary to rely on waqf, where this can be an alternative in solving the socio-economic problems of the people which include problems of poverty, inequality and increasing costs of living as well as in promoting social welfare in society.